Edición génica porcina para xenotrasplante mediada por la inyección intracitoplasmática de espermatozoide - Briski, Olinda (2023)
Xenotransplantation could be used to overcome the current shortage of organs for transplants. The technique consists of using animal (e.g. pig) organs to transplant them into \nhuman beings. Pigs are considered excellent candidates for xenotransplantation due to their anatomical and physiological similarities with the human species, as well as the facility to reproduce and keep them under appropriate biosecurity conditions. However, multiple genetic \nmodifications of the pig genome will be necessary to reduce immunologic organ rejection in order for xenotransplantation to be viable. The development of the CRISPR-Cas9 system has \nenabled testing genetic modifications through various embryo production techniques, such as \nsomatic cell nuclear transfer, oocyte or zygote microinjection, or electroporation derived from \neither in vitro fertilization (IVF) or in vivo fertilization. In this thesis, we propose the use of intracytoplasmic sperm injection mediated gene editing (ICSI-MGE) to produce genetically \nedited embryos, which has not been a broadly used alternative so far. ICSI-MGE consists in the co-injection of the spermatozoon together with the CRISPR-Cas9 system in a mature oocyte. ICSI-MGE was used in this thesis to inactivate certain genes that encode enzymes \nresponsible for the hyperacute immunological rejection generated during pig-to-human \nxenotransplantation, such as alpha-1,3-galactosyltransferase (GGTA1), citidine \nmonophosphate N-acetylneuraminic acid hydrolase (CMAH) and beta-1,4-N-acetyl galactosaminil transferase 2 (4GalNT2). Concurrently, we sought to inactivate the gene that codes for the growth hormone receptor (GHR) in order to limit the growth of the pig for its organs to be similar in size to those of the human being. This is an indispensable requirement for future heart transplants. \nThe initial experiments focused on optimizing porcine ICSI and exploring its biological limitations. Porcine ICSI has the advantage of avoiding polyspermy, which is very frequent in porcine IVF. However, the blastocyst rates obtained were still low (8.4 to 22%), which could be related to various causes, such as incomplete sperm decondensation and/or alteration in the oocyte activation mechanism. Consequently, as initial measures we proposed to improve \nthe two-pronucleus formation rates (2-PN) by using the piezo-drill (ICSIp), the electrically \nassisted activation (ICSIe) and the chemically assisted activation with the zinc chelator 1,10-\nphenantroline (PHEN) (ICSI-phen). The results showed that neither ICSIe, ICSIp or ICSI-phen improved the 2-PN formation rates compared to conventional ICSI (ICSI). ICSI-phen resulted \nin higher activation rates than conventional ICSI (82.5% and 55.88%, respectively), but it did \nnot contribute to the decondensation of the spermatozoon. Subsequently, we evaluated the embryo development to blastocyst comparing ICSI with ICSI-phen and no significant \ndifferences were found in the blastocyst rates (ICSI=13.85%; ICSI-phen=20.5%) or in their \nquality after evaluating the expression pattern of pluripotency markers. This demonstrated that, \nwhile PHEN does not produce improvements, it does not have negative effects on the amount \nor quality of the embryo either. In summary, the proposed strategies to improve the efficiency \nof porcine ICSI do not increase the 2-PN formation rates, nor the blastocyst rates or their \nquality. In addition, artificial assisted activation showed certain risk of parthenogenetic embryo \nproduction, and its use was therefore not considered in future experiments in this thesis. \nThe final goal of the thesis was to use ICSI-MGE to produce genetically edited pigs and compare embryo developmental rates, embryo gene editing rates, and birth rates of edited \npiglets with those resulting from two other techniques: i) oocyte microinjection followed by IVF,\nand ii) zygote microinjection produced by in vivo fertilization with CRISPR-Cas9 system. Our \nresults showed that ICSI-MGE was efficient in editing the GGTA1 gene, as 100% of the embryos were edited (15/15), comparable to the efficiency registered by microinjection of the \noocyte and subsequent IVF (16/16). The viability of the embryos fertilized in vivo and microinjected with CRISPR-Cas9 was higher than for the other two experimental groups: it was the only group from which five offspring were born following the surgical transfer of the embryos to a recipient female. The five born piglets presented editions in both alleles of the GGTA1 gene. Furthermore, three of these piglets also presented an edited GHR gene, one biallelic and the other two monoallelic. No effective editions for the CMAH and 4GalNT2 \ngenes were observed neither in the blastocysts obtained (regardless of which of the three\ntechniques is used) nor in the born piglets. \nIn conclusion, it is possible to generate blastocysts with high mutation rates through \nICSI-MGE. This technique is presented as an alternative and a solution to the polyspermy resulting from porcine IVF. Additionally, ICSI-MGE can be a very useful solution in various scenarios, such as a limited availability of male samples of high genetic value (and/or if they are genetically modified), as well as in cases in which semen shows poor response to cryopreservation or poor sperm quality and is thus unable to achieve fertilization through IVF \nor artificial insemination. However, although ICSI-MGE mutation rates are higher than those obtained by microinjection of embryos fertilized in vivo, the viability of embryos produced in vitro is yet to improve by standardizing culture media for porcine, which is an important step for the viable production of genetically edited pigs. Obtaining embryos fertilized in vivo requires \ngreater logistics and effort when compared to the production of embryos with in vitro techniques, and the mutation rates are lower as well. However, it was the technique that proved \nefficient for the birth of five edited pigs. While more tests will be required to obtain all of the \nproposed modifications simultaneously, they are the first genetically edited pigs achieved in Latin America and contribute a significant advance in pig production for xenotransplantation